Students as active learners on their assessment process in an acrobatic gymnastics unit: study in preservice physical education teachers’ school placement (Revista Infancia, Educación y Aprendizaje, 2019)
This study intends to analyse how students’ involvement in their assessment process contributes to their learning in a gymnastics acrobatic unit. It took place during the school placement of two physical education preservice teachers. Their classes had 43 students (23 girls and 20 boys) with ages between 15-17 years old. Students were challenged to build a choreography, according to the dossier delivered at the first class that contains objectives, contents, assessment criteria, and assessment forms. Data were collected from assessment forms, fulfilled by students at the end of each class and analysed by the preservice teachers before the next class; assessment of the choreography built by students and a written test. Students showed active involvement along all the process, taking advantage of their self-assessment to improve their performance. Sharing assessment criteria and learning objectives with the students contributed to improving their learning about acrobatic gymnastics.